Future of Indonesia’s Industrial R&D using system dynamics - Erman Aminullah (National Research and Innovation Agency, Indonesia, 2026)
This study attempts to explore the future of Indonesia's industrial R&D intensity based on historical data trends. A systemic approach and system dynamics modelling were used to explain Indonesia's high reliance on public funding for R&D activities. The simulation results show that: i. the policy of increasing industrial R&D investment can be implemented by transferring research outputs from research institutions to the industrial sector, as well as increasing R&D investment in the mission-oriented industrial sector. This is a challenging scenario for the most ambitious future R&D trends by 2045. ii. Limited R&D spending can have a tangible economic impact if public R&D organisations implement researcher performance evaluations based on R&D results' application in industry. Transferring government R&D outputs to the industrial sector will boost future industrial R&D in a moderate scenario by 2045. iii. Prolonged reliance on government R&D funding has the unintended consequence of lock-in dependence on public R&D funding, and further delays in increasing industrial R&D trends are most likely in a BAU scenario by 2045. The long-term policies should be executed integrally in realizing Indonesia’s transition to industrial R&D. This study's scientific contribution is a model of lock-in dependence on public R&D funding based on historical data.